2014
DOI: 10.1080/14765284.2013.875289
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between IFRS, earnings losses threshold and earnings management

Abstract: An increasing number of countries have adopted International Financial Reporting Standards (IFRS). Prior research indicates that IFRS increase the relevance of financial statements, but also increase opportunism in earnings management (EM). Despite this, no evidence is found in this study to demonstrate that the adoption of IFRS increases the use of EM by companies as a whole. Furthermore, the results indicate that the use of IFRS can enhance the neutrality of financial statements. However, these phenomena occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…High reporting standard does not necessarily produce good quality of accounting information because it is also determined by the incentive level of the financial reporter, economic and politic factor (Ball, Robin, & Wu, 2003;Maulana, Salim, & Aisjah, 2015 Donnelly 2016found that financial reporting quality is not affected by the adoption of IAS/IFRS. Also, Kao (2014) found that higher audit quality does not help to a constraint on earnings manipulation but the increase the level of earnings management for IFRS adopters with income-decreasing earnings management. The results of this study are consistent with the result of some researchers (Ball, Robin, & Wu, 2003;Ismail, Kamarudin, Zijl, & Dunstan, 2013;Jeanjean & Stolowy, 2008).…”
Section: Resultsmentioning
confidence: 93%
“…High reporting standard does not necessarily produce good quality of accounting information because it is also determined by the incentive level of the financial reporter, economic and politic factor (Ball, Robin, & Wu, 2003;Maulana, Salim, & Aisjah, 2015 Donnelly 2016found that financial reporting quality is not affected by the adoption of IAS/IFRS. Also, Kao (2014) found that higher audit quality does not help to a constraint on earnings manipulation but the increase the level of earnings management for IFRS adopters with income-decreasing earnings management. The results of this study are consistent with the result of some researchers (Ball, Robin, & Wu, 2003;Ismail, Kamarudin, Zijl, & Dunstan, 2013;Jeanjean & Stolowy, 2008).…”
Section: Resultsmentioning
confidence: 93%
“…The insignificant relation is due to the contention that IFRS adoption in isolation does not significantly improve accounting quality but rather compliance to the standards leads to increased accounting quality as established in the studies of Mbir et al (2020). Buttressing this point Kao (2014) reiterates that management are likely to engage in earnings manipulations when faced with negative earnings while Jeanjean and Stolowy (2008) ascribe the insignificant relation to the prevailing lax implementation of regulations by institutions and managerial incentives.…”
Section: Regression Results (Ordinary Least Square Regression) 431 Th...mentioning
confidence: 98%
“…Apparently, this research finds diverse studies conducted in the past couple of years in China, highlighting numerous issues associated with IFRS enforcement (Peng & Smith, 2010;Ping, 2008;, enforcement of IFRS (Ding & Su, 2008;Wang et al, 2012), fair value measurement issues (Peng & Bewley, 2010;Zhang et al, 2012), earnings management (Cang et al, 2014;Kao, 2014;Zhang et al, 2013), etc., but the literature is limited for other Brazil, Russia, India and China (BRIC) nations like Brazil, India and Russia. In India, according to Dhankar and Gupta (2014), the Advisory Committee on Accounting Standards (NACAS) published a deferral in enforcing the Ind-AS, which were cited as the pending modifications and settlement of diverse regulatory and taxation issues in addition to pitfalls inherent in IFRS convergence mechanism such as awareness, training and cost of implementation.…”
Section: Review Of Literaturementioning
confidence: 94%